Background of the professionalization of health administration at UNED, Costa Rica (Revista Electrónica Calidad en la Educación Superior, 2024)
Introduction: In Costa Rica, Health Services Administration career was born in 1985, but lacks historical documentation. Objective: Describe the main events that revolve around the birth of this profession in Costa Rica. Results: The need for professionalization in the discipline was recognized since 1979; subsequently, UNED had to choose between different health professionalization options. The market study was analyzed from two perspectives, due to the limited vision with which it was proposed. The target population was defined in an inclusive way. The career curricula was approved in 1985. Conclusion: There is a need to follow up on proposals for bibliographic collection, which will allow to improve the careers’ management.
Keywords: Higher education; History; Professional training; Health services